Discovery of F-18 labeled repurposed CNS drugs by computational strategy for effective tau imaging and alzheimer’s diagnosis - Pan Tang; Xuehua Chen; Pingping Li; Ling Zhang; Bin Tang; Jun Wen; Yan Liu; Iqra Kalsoom; Chong Cheng (PLoS ONE, 2025)
Alzheimer’s disease (AD) remains a significant challenge in diagnosis and treatment, with current methods insufficient for early detection. A major obstacle is the lack of effective imaging agents targeting the Tau protein, which plays a key role in AD pathology. To address this, we developed a computational methodology for selecting F-18 labeled drug candidates from a library of CNS-penetrant compounds curated from literature and databases. The library, consisting of 977 compounds, was evaluated based on clinical data, target proteins, pathways, toxicity, and other relevant factors. We implemented Python-based algorithms to select the top 39 compounds from virtual screening results, prioritizing those with optimal Tau binding affinity and BBB permeability. Additionally, we developed an algorithm to identify F-18 labeling candidates that maintain their biological activity post-labeling. We then performed virtual screening of an F-18 labeled drug library and selected the top 3 compounds based on stability and imaging potential. The selected compounds exhibited molecular weights of 350–520 Da, favorable logP values (2.05–2.72), and high BBB permeability. Our findings indicate that Drug 388 (BI-D1870), binds to Tau with a binding free energy of ΔG = −8.79 kcal/mol. Drug 416 (reported BRAF inhibitor, RG6344) shows a binding free energy of ΔG = −7.91 kcal/mol, while Drug 610 (Iloperidone/HP 873), a D2/5-HT2 receptor antagonist, exhibits a predicted binding free energy of ΔG = −6.88 kcal/mol with the target Tau protein respectively. Molecular dynamics simulations confirmed stable Tau-drugs interactions, with minimal RMSD fluctuations, indicating strong binding. The F-18 label enabled real-time PET imaging, allowing non-invasive tracking of the drug’s binding to Tau in the brain. Our approach provides a comprehensive solution to the current limitations in Alzheimer’s diagnosis by offering F-18 labeled drugs that effectively target Tau protein without compromising their biological activity, advancing both diagnostic and therapeutic strategies for AD.